Reward Management and Organizational Commitment in Tribhuvan University: An Empirical Study - Kharel, Shreekrishna; Niraula, Ganesh Prasad; Mainali, Bhawani Prasad (Journal of Nepalese Management Academia, 2024)
In the current business environment, organizational commitment is receiving widespread attention for all kinds of organizations. This study aims to investigate the relationship between Tribhuvan University faculty members’ organizational commitment and reward management. The study’s independent variables are job evaluation, team support, supervision, and promotion opportunities. The dependent variable in the study is organizational commitment. In this study, a survey research design is utilized. The population survey included 7966 faculty members, 569 of whom were selected as sample based on judgmental sampling from 62 constituent campuses of Tribhuvan University. The information was gathered using a standardized Likert scale questionnaire, where 1 represented a strong disagreement and 5 represented a strong agreement. Regression analysis and correlation analysis were used to analyze the data. Reliability has been measured using Cronbach’s Alpha. Reliability has an average Chronbach’s Alpha of 0.862, which is considered adequate. SPSS version 27 has been used to analyze the data. According to the study, job evaluation has no impact on organizational commitment, but team support, supervision, and promotional opportunities all positively and significantly associated to organizational commitment. The primary focus of this study is the necessity of proactive, all-encompassing tactics to reward management practices in order to ensure faculty dedication in Tribhuvan University and prioritize organizational commitment.